M&A open innovation, and its obstacle: A case study on GCC region - Wardah Bindabel (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Considering the effective growth in challenges and an urge in establishment for sustainable business, companies trading globally are inclined towards the implementation of highly efficient cross-border reallocations of revolving capital. The prominent objective of this research paper is therefore the clear identification of the active key attributes and specifications of all strategic measures for efficient sustainable cross-border mergers and acquisitions (M&As) of the Islamic companies in the Gulf region that are keen to engage with the non-Islamic companies across the globe. This paper also explores the paradigm of culture, in its different manifestations, it was and still is a primary factor of creativity. This study also focuses on building some better understanding of the role of "Culture for Open Innovation Dynamics." Initially, since the need to interpret community, that can also influence the dynamics of open innovation, has sharply increased, the research addresses open innovation dynamics and its significant concerns related to cross border mergers and cross culture ventures of firms and organizations. The researcher purposively selected 15 financial institutions from the selected Gulf Cooperation Council (GCC) countries. Semi-structured interviews were conducted with 40 key individuals including Board of Directors (BOD) members, lawyers and the Shariah scholars involved with three Islamic banks and two Islamic insurance companies in GCC. The findings indicate a consensus among the respondents regarding how the Shariah corporate governance principles can present barriers for cross-border M&As. Key obstacles to the success of cross-border M&As between the Islamic and the non-Islamic companies include the Shariah compliance, weak systems of disclosure, dependency, corruption in compliance, having family members on the Board, weakened communication with external auditors, different interpretations of Shariah by different scholars and a lack of alternative Islamic financial instruments. The comprehensive research in this paper fills the research gap by specifying the key attributes of considering the future implementation and management of M&As in broader scopes.
Keywords: 650; open innovation; corporate culture; diversity; international business administration; mergers and acquisitions; sustainable business